2013
DOI: 10.1111/resp.12153
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of cigarette smoking in Japanese patients with sarcoidosis

Abstract: This retrospective cohort study suggests that smoking prevalence is higher in Japanese sarcoidosis patients than that reported in Western sarcoidosis patients and that there could be different relationships between smoking and the development of sarcoidosis in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Nonetheless, it should be noted that the negative association between smoking and sarcoidosis has not been observed in Asian cohorts [14, 15]. It is possible that different etiopathogeneses are responsible for the development of sarcoidosis different regions/populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it should be noted that the negative association between smoking and sarcoidosis has not been observed in Asian cohorts [14, 15]. It is possible that different etiopathogeneses are responsible for the development of sarcoidosis different regions/populations.…”
Section: Discussionmentioning
confidence: 99%
“…Hattori et al . sought to assess the relationship between sarcoidosis and cigarette smoking in Japan . In contrast with other studies undertaken, they found a strikingly high rate of smoking in their sarcoid patients (59.6% in men and 27.9% of women).…”
Section: Interstitial Lung Diseasesmentioning
confidence: 90%
“…Findings of chest radiographs taken at the 2‐ or 5‐year observation points were retrospectively evaluated independently by two respiratory physicians who were blinded to all other clinical information of the subjects. Disagreements between the two physicians were resolved on the basis of a majority decision after review by a third respiratory physician …”
Section: Methodsmentioning
confidence: 99%
“…The presence of organ involvement was defined as previously described. 20 Briefly, pulmonary involvement was defined when chest radiographs showed abnormality according to the Scadding system. 7 Ocular involvement of sarcoidosis, including uveitis, was diagnosed by ophthalmologists.…”
Section: Evaluation Of Organ Involvement and Clinical Course Of Sarcomentioning
confidence: 99%
See 1 more Smart Citation